2021
DOI: 10.1016/j.str.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.2 EFL domain allosterically enhances Ca2+ binding to sites I and II of WT and pathogenic calmodulin mutants bound to the channel CTD

Abstract: Na V 1.2 EFL domain allosterically enhances Ca 2+ binding to sites I and II of WT and pathogenic calmodulin mutants bound to the channel CTD Graphical abstract Highlights d In solution, only the IQ motif of Na V 1.2 CTD(1,777-1,937) contacts CaM ± Ca 2+ d Ca 2+ changes interfaces of CaM + Na V 1.2-IQ p and CaM + Na V 1.2-CTD complexes identically d Ca 2+ binds to N-domain sites of CaM + Na V 1.2-CTD preferentially relative to free CaM d Apo pathogenic CaM mutants bind the Na V 1.2 CTD as well or better than WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 140 publications
(178 reference statements)
1
2
0
Order By: Relevance
“…In this study, we demonstrated p.N138K decreases Ca 2+ -binding affinity, but the degree was not as much as that of p.D130G in literature. 8,27 This result well reflects the different effect of 2 variants on CaM structure. Of course we cannot exclude that in vivo the p.N138K defect could be rescued by some target proteins such as kinases and other channels regulated by CaM.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we demonstrated p.N138K decreases Ca 2+ -binding affinity, but the degree was not as much as that of p.D130G in literature. 8,27 This result well reflects the different effect of 2 variants on CaM structure. Of course we cannot exclude that in vivo the p.N138K defect could be rescued by some target proteins such as kinases and other channels regulated by CaM.…”
Section: Discussionsupporting
confidence: 60%
“…Although there is a Ca 2+ -binding EFL motif upstream of the IQ domain in the Na v 1.2 channel, the Ca 2+ -mediated changes in modification of Na v 1.2 function are proposed to be likely from the interaction between CaM and Na v 1.2 IQ domain when Ca 2+ binding to CaM. The Na v 1.2 channel EFL motif was indicated to enhance Ca 2+ binding to CaM interacting with the channel [41].…”
Section: Na V 12mentioning
confidence: 96%
“…For example, the binding of calmodulin (CaM) to the C‐terminal domain of the neuronal voltage‐gated sodium channel Na V 1.2 regulates the channel activity and inactivation, which are crucial for the initiation and propagation of action potentials in neurons 6 . Mahling et al 7 showed that human Na V 1.2 bound tightly to apo CaM whereas bound Ca 2+ reduced the affinity in the CaM‐binding sites. Shihoya et al 8 reported that the endothelin 1 (ET‐1)‐endothelin receptor (ET B ) complex has a large interacting surface area, which accounts for the exceptionally high affinity for ET‐1 with K d on the sub‐nanomolar order.…”
Section: Introductionmentioning
confidence: 99%